157k views
4 votes
Find the solutions to the following equation. Answers as ordered pairsx^2 + 6x + 5 = 0

1 Answer

5 votes

x² + 6x + 5 = 0

To find the solution, we can use the quadratic formula.


\begin{gathered} x_(1,2)=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ x_(1,2)=\frac{-6\pm\sqrt[]{6^2-4(1)(5)}}{2(1)} \\ x_(1,2)=\frac{-6\pm\sqrt[]{36^{}-20}}{2} \\ x_(1,2)=(-6\pm4)/(2) \\ x_1=(-6+4)/(2)=-1 \\ x_2=(-6-4)/(2)=-5 \end{gathered}

The solutions are (-1, 0) and (-5, 0)

User ASHWIN RAJEEV
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.